Designing Shape Morphing Behavior through Local Programming of Mechanical Metamaterials - Wenz, Franziska; Schmidt, Ingo; Leichner, Alexander; Lichti, Tobias; Baumann, Sascha; Andrae, Heiko; Eberl, Christoph (Advanced materials (Weinheim), 2021)
Shape morphing implicates that a specific condition leads to a morphing reaction. The material thus transforms from one shape to another in a predefined manner. In this paper, not only the target shape but rather the evolution of the material's shape as a function of the applied strain is programmed. To rationalize the design process, concepts from informatics (processing functions, for example, Poisson's ratio (PR) as function of strain: ν = f(ε) and if‐then‐else conditions) will be introduced. Three types of shape morphing behavior will be presented: (1) achieving a target shape by linearly increasing the amplitude of the shape, (2) filling up a target shape in linear steps, and (3) shifting a bulge through the material to a target position. In the first case, the shape is controlled by a geometric gradient within the material. The filling kind of behavior was implemented by logical operations. Moreover, programming moving hillocks (3) requires to implement a sinusoidal function εy = sin (εx) and an if‐then‐else statement into the unit cells combined with a global stiffness gradient. The three cases will be used to show how the combination of mechanical mechanisms as well as the related parameter distribution enable a programmable shape morphing behavior in an inverse design process. Different kinds of shape morphing are realized with programmable materials. Therefore, processing functions as well as if‐then‐else‐conditions are implemented in unit cells. Local geometrical adaptions allow controlling the global shape in dependency of a load amplitude. Combining these elements, (strain‐dependent) shapes as well as a moving hillock are created within a material.